A Tuning‐Fork Triboelectric Nanogenerator with Frequency Multiplication for Efficient Mechanical Energy Harvesting. Issue 5 (29th March 2022) - Liu, Nian; Liu, Di; Gao, Yikui; Li, Shaoxin; Zhou, Linglin; Zhao, Zhihao; Cui, Shengnan; Liu, Lu; Wang, Zhong Lin; Wang, Jie
Abstract: As a new technology for high‐entropy energy harvesting, a triboelectric nanogenerator (TENG) has broad applications in sensor networks and internet of things as a power source, but its average power density is limited by the fixed low‐frequency output. Here, a frequency‐multiplication TENG based on intrinsic high frequency of tuning fork is proposed which enables converting low‐frequency mechanical energy into high‐frequency electric energy. A tuning‐fork TENG is used to systematically study the effects of intrinsic frequency, dielectric's thickness, and gap distance on its electric performance, and a total transferred charges of 4.3 µC and an average power density of 9.42 mW m –2 are realized at the triggering frequency of 0.2 Hz, which are 71 times and 5.7 times than that of the single‐cycle output of conventional contact‐separation TENG, respectively. Moreover, the crest factor also decreases from 3.5 to around 1.5. Then, a homemade tuning fork‐like TENG is reasonably designed for harvesting ambient wind energy, achieving an average power density of 20.02 mW m –2 at a wind speed of 7 m s –1 . Specially, its impedance resistance is independent of the mechanical triggering frequency, simplifying the back‐end power management circuit design. Therefore, the frequency‐multiplication TENG shows a great potential for efficient distributed energy harvesting. Abstract : An easy frequency‐multiplication method based on the intrinsic frequency of tuning‐fork is proposed to improve the comprehensive performance of a triboelectric nanogenerator (TENG). The tuning‐fork TENG can convert the low‐frequency mechanical energy to high‐frequency electric energy, enabling increasing the total output charges, improving average power density, decreasing the current crest factor, and reducing the matched impedance resistance.